2018
DOI: 10.3846/bjrbe.2018.383
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Recycled Asphalt Pavement on Properties of Foamed Bituminous Mixtures

Abstract: Abstract. In recent years, the use of foamed bitumen technology along with Reclaimed Asphalt Pavement is gaining popularity across the world. The mechanical response of foamed bitumen mixtures containing reclaimed asphalt pavement is significantly influenced by constituent material properties and aggregate gradation. This article presents results from a study where foamed bitumen mixtures conforming to Indian specifications were evaluated. For this purpose, foamed bitumen mixtures using a different percentage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…When the dose of capsules continues to increase, the mechanical properties will be seriously reduced, even unable to meet the relevant speci cations [1,2]. Lot and research found that the fatigue life of modi ed asphalt mixture is greatly improved compared with conventional mixture [3,4]. Kar believes that among the different mixtures, the mixture containing 50% recycled asphalt pavement shows the best results in the elastic modulus and moisture damage resistance tests.…”
Section: Introductionmentioning
confidence: 99%
“…When the dose of capsules continues to increase, the mechanical properties will be seriously reduced, even unable to meet the relevant speci cations [1,2]. Lot and research found that the fatigue life of modi ed asphalt mixture is greatly improved compared with conventional mixture [3,4]. Kar believes that among the different mixtures, the mixture containing 50% recycled asphalt pavement shows the best results in the elastic modulus and moisture damage resistance tests.…”
Section: Introductionmentioning
confidence: 99%
“…Marshall’s method of compaction is very well considered for preparing the specimen of the hot bituminous mix in the Indian standard codes. In addition, some literature (Technical Guideline-2, 2009; Kar et al , 2017a; Modarres and Ayar, 2016) has also suggested the Marshall method of compaction (75 number of blows) to achieve the optimum binder content in association with maximum dry density to prepare the cold mix specimen. Moreover, Loizos and Papavasiliou, (2006) have also been advocated a change in design pattern from the Marshall method of mix design to a design based on performance criteria; resilient modulus, moisture resistance and indirect tensile strength for the design of cold bituminous mix.…”
Section: Introductionmentioning
confidence: 99%
“…Asphalt Recycling and Reclaiming Association; it has defined different recycling techniques such as Cold Planing, Hot Recycling, Hot In-Place Recycling, Cold Recycling, Full Depth Reclamation [3]. Considering the increase in greenhouse gas emissions by twice every 10 ° C in the production of bituminous mixtures [4], cold recycling from these methods undoubtedly stands out due to its environmental advantages [5], [6]. The main logic in recycling with foam bitumen, which is one of the recycling methods in the cold in place, is to increase the surface area of the bitumen to facilitate its mixing into recycled material [7].…”
Section: Introductionmentioning
confidence: 99%